Impact of the omicron phase on a highly advanced medical facility in Japan - Yamagishi, Hirokazu; Tamura, Daisuke; Aoyagi, Jun; Suzuki, Shun; Mizobe, Yoshitaka; Wakae, Keizo; Yamagata, Takanori; Tajima, Toshihiro; Osaka, Hitoshi (Frontiers in Pediatrics, 2023)
Background: Eight waves of the coronavirus disease 2019 (COVID-19) epidemic have been observed in Japan. This retrospective study was conducted to clarify the clinical characteristics of pediatric COVID-19 patients. Methods: We studied 121 patients admitted to the Jichi Children's Medical Center Tochigi between April 2020 and March 2023. Incidence of pediatric COVID-19 in Tochigi Prefecture was used to examine hospitalization and severe illness rates. Results: The mean age of the patients was 3 years and 8 months. One hundred and eleven patients (91.7%) were hospitalized after January 2022 (after the 6th wave), when the Omicron strain became endemic in Japan. Convulsions occurred in 30 patients (24.8%), all of whom were admitted after the 6th wave. Twenty-three of the 30 patients had no underlying disease. Eleven patients (9.1%) were diagnosed with acute encephalopathy. One patient died due to hemorrhagic shock and encephalopathy syndrome and two had sequelae after the 6th wave. The patient who died due to encephalopathy had hypercytokinemia. In the Tochigi Prefecture, the number of pediatric COVID-19 patients increased after the 6th wave, but the hospitalization rate declined. The rate of severe illness did not change before the end of 5th and after the 6th wave. Conclusion: Although the rate of severe illness in patients with pediatric COVID-19 did not increase after the 6th wave, some patients had complicated critical illnesses. Systemic inflammatory reaction was considered to have been associated with the severe encephalopathy.